Exchange rates, labour costs and international competitiveness - Heinz Salowski (Intereconomics, 1982)
The international competitiveness of German industry, so greatly dependent on exports, is in large measure determined both by fluctuations in the rate of exchange and by the level of its labour costs in relation to those of its competitors in the world market. Recent trends in these two factors are discussed in the following article.
Keywords: 330